The Effect of Selebgram Endorsement, Online Marketing, and Online Ojek Existence on Muslim Micro, Small and Medium Enterprises (MSMEs) Income in Panyabungan, Mandailing Natal Regency - Nasution, Rizka; Nasution, Yenni Samri Juliati; Nasution, Muhammad Lathief Ilhamy (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The aspects of the problem studied by the author are regarding the influence of celebrity endorsements, online marketing, and the existence of online motorcycle taxis on the income of Micro, Small and Medium Enterprises (MSMEs) in Panyabungan, Mandailing Natal Regency. The purpose of this study was conducted to determine the effect of celebrity endorsements, online marketing, and the existence of online motorcycle taxis on the income of Micro, Small and Medium Enterprises (MSMEs) in Panyabungan, Mandailing Natal Regency. The data analysis technique used is the quantitative method. Data collection was carried out by distributing questionnaires and the results of the questionnaires were received back for processing. Data were analyzed using SPSS 20. The results of the study based on the t test showed that celebrity endorsements had no significant effect on Micro, Small and Medium Enterprises (MSMEs) income, online marketing had a significant effect on Micro, Small and Medium Enterprises (MSMEs) income, and the presence of online motorcycle taxis had no effect. significantly to the income of Muslim Micro, Small and Medium Enterprises (MSMEs), and the results of research based on the F test show that celebrity endorsements, online marketing, and the existence of online motorcycle taxis simultaneously have a significant effect on the income of Muslim Micro, Small and Medium Enterprises (MSMEs) with a coefficient of determination of 61, 2%. The results of statistical tests show that there is an influence of celebrity endorsements, online marketing, and the existence of online motorcycle taxis on the income of Muslim Micro, Small and Medium Enterprises (MSMEs) in Panyabungan, Mandailing Natal Regency.